MANFAAT VAKSINASI DAN PENCEGAHAN MALARIA PADA WISATAWAN DENGAN PERJALANAN INTERNASIONAL: KAJIAN PUSTAKA DALAM PERSPEKTIF KEPERAWATAN - Raya, Nyoman Agus Jagat (Coping: Community of Publishing in Nursing, 2016)
Travelers who have international travel to high risk area of communicable disease should be consulted on the preparation of health-related travel frequently. Vaccinations and malaria prevention information are some of the ways that travelers can do before traveling internationally. The purpose of this paper to describe the literature review on the role of nurses to the existence of vaccination and prevention of malaria in travelers who will travel internationally. Method of this paper by searching several publications and journal articles from electronic databases and search on the internet, from 2013 to 2016. HAV and HBV vaccination should be given to travelers who will travel internationally because they provide benefits to the immune system. Prevention can be done to travelers  who visiting the area with the incidence of malaria, such as by chemoprophylaxis, insect bite treatment, perform rapid diagnostic test, and consultation before departure (pre-travel) to give travel information on health-related travelers. The role of the nurse can be applied prior to departure or post-arrival, such as educators, managers, preventive and nursing care providers.   Keywords: International, Malaria, Nurse, Traveler, Vaccination